Efficacy and Safety of Dead Sea-Derived Components in Oral Health Applications: A Systematic Review - Elisabetta Ferrara; Giovanna Murmura; Manlio Santilli; Bruna Sinjari (Traditional and Integrative Medicine)
The therapeutic potential of Dead Sea-derived components in oral health management has gained increasing attention, yet remains largely unexplored. This systematic review aimed to evaluate the efficacy and safety of Dead Sea-based products in oral health applications. A comprehensive literature search was conducted in PubMed, Scopus, and Web of Science databases for studies published up to March 2023, yielding seven studies that met the inclusion criteria. The evidence suggests potential benefits of Dead Sea-derived products in managing periodontal conditions and chemotherapy-induced oral mucositis. Randomized controlled trials demonstrated that Dead Sea salt-containing mouthwashes significantly reduced plaque and gingival indices compared to controls, with efficacy comparable to chlorhexidine in some cases. An observational study reported reduced mucositis intensity in cancer patients using Dead Sea mineral products. In vitro research showed Dead Sea salt solutions reduced concentrations of bacterial leukotoxin, lipopolysaccharide endotoxin, and glucan sucrase. A clinical trial found significant reductions in salivary viral loads with a Dead Sea salt-based mouthwash. However, a Dead Sea salt-based tooth whitening regimen was less effective than conventional peroxide treatment. The unique mineral composition and microbiological characteristics of the Dead Sea appear to confer antimicrobial and anti-inflammatory properties. Nevertheless, the evidence is limited by the small number of studies, their heterogeneity, and lack of long-term follow-up data. Further research is needed to establish the long-term efficacy and safety of these products in oral health care.